1986
DOI: 10.2307/3576804
|View full text |Cite
|
Sign up to set email alerts
|

The Range of High LET Effects from 125 I Decays

Abstract: Track structure techniques are applied to calculate energy depositions in cylindrical targets 20 A in diameter (simulating the DNA duplex) containing, or near, 125I decays. Two problems are examined: (1) The possible effects of incorporated versus nonincorporated 125I are evaluated; (2) the extent of the radiological damage along the DNA is described and discussed for individual decays taking place in the DNA. The results of three different calculations are presented: (1) The distribution of the total energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 8 publications
2
47
0
1
Order By: Relevance
“…From the viewpoint of their cell-killing potential, the advantage of Auger electron-emitting radionuclides is their extremely short range and localized dose deposition. New strategies are being developed for delivery of Auger electron-emitting radionuclides to the nucleus, such as carbon nanotubes (33), gold nanoparticles (34), antibody-based peptides (35), and cell-penetrating peptides (36). Intranuclear delivery of Auger electron-emitting constructs results in relative biological effectiveness similar to that of a emitters but with a reduced crossfire effect compared with a emitters, making them more suitable for single-cell irradiation (9).…”
Section: Discussionmentioning
confidence: 99%
“…From the viewpoint of their cell-killing potential, the advantage of Auger electron-emitting radionuclides is their extremely short range and localized dose deposition. New strategies are being developed for delivery of Auger electron-emitting radionuclides to the nucleus, such as carbon nanotubes (33), gold nanoparticles (34), antibody-based peptides (35), and cell-penetrating peptides (36). Intranuclear delivery of Auger electron-emitting constructs results in relative biological effectiveness similar to that of a emitters but with a reduced crossfire effect compared with a emitters, making them more suitable for single-cell irradiation (9).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is less efficient in the production of DNA double-strand breaks [0.74 compared with 1.00 per cell per decay for 1251 (Makrigiorgos et al, 1992) The conventional opinion is that the critical cellular target for ionizing radiation damage is nuclear DNA. Therefore, ultra-shortrange radionuclides, such as Auger electron emitters, should be toxic only if delivered to the nucleus of the target cell (Charlton, 1986). This has been confirmed by in vitro studies -using extracellular Na'251, cytoplasmic [1251]iododihydrorhodamine and nuclear '25IUdR -which demonstrated that significant toxicity was associated only with the nuclear located 1251 (Kassis et al, 1987 (1998) 77(12), [2061][2062][2063][2064][2065][2066][2067][2068] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the high-LET-type radiotoxicity of DNA-incorporated Auger emitters has been well established (4,10,25,26), direct experimental comparisons with the densely ionizing high-LET radiations such as α particles have become available only recently through the in vivo and in vitro work of Rao et al (9) and Howell et al (11). For spermatogonial cell killing (9), RBE values of 7.9 ± 2.4 and 6.7 ± 1.4 were obtained for 125 IUdR and 210 Pocitrate, respectively, indicating that the dense shower of Auger electrons from DNAbound 125 I decays is as lethal as 5.3-MeV α particles emitted by 210 Po.…”
Section: High-let Response: Auger Emitters Vs α Emittersmentioning
confidence: 99%